Generalized contest success functions - Birendra K. Rai; Rajiv Sarin (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The key element of models of contest is the Contest Success Function (CSF) which specifies the winning probabilities of agents. The existing axiomatizations of CSFs assume that contestants can make only one type of investment. This paper generalizes these axiomatizations to the case where each agent can have multiple types of investments. This allows us to provide a unified framework to extend and interpret the results of Skaperdas (1996) and Clark and Riis (1998), and rationalize some seemingly ad hoc CSFs used by applied researchers.
Keywords: C70; D72; D74; 330; Contest; Rent Seeking; Spieltheorie; Rent Seeking; Theorie